EFFECT OF FRESH AND FERMENTED OLIVE SOLID WASTE AND COW MANURE ON IRON FORMS IN CALCAREOUS SOIL AND WHEAT PLANT PRODUCTIVITY - & Al -Balkhi, Jaafar (IRAQI JOURNAL OF AGRICULTURAL SCIENCES, 2020)
A field experiment was conducted at the farm of Abu Jarash at the Agricultural College, using different rates of olive solid waste and cow manure, as follows: (control, Mineral fertilizer +NPK, fresh olive solid waste100%, fresh olive solid waste 75%+ cow manure 25%, fresh olive solid waste 50%+ cow manure 50%, fermented olive solid waste 100%, fermented olive solid waste 75%+ cow manure 25%, fermented olive solid waste 50%+ cow manure 50%, cow manure 100%). Iron fertilizer had been added as iron sulfate in equal amount for each treatment. the fermented olive solid waste 100% treatment was Superiority in the amount of iron forms as following: (total, soluble, exchanged, linked with carbonate bound, organic matter bound iron and manganese oxides bound and residual) the iron amounts were (1296, 0.29, 2.25, 7.74, 37.90, 289.1 and 958.75) mg/kg-1 in the same previous order. While the iron values ​​in the treatment of the control were (1174, 0.188, 1.111, 732, 29.43, 260.5, 875.8) mg kg-1 for the same forms and in the same previous order. The fermented olive solid waste treatment 100% had the highest yield (5.980) ton h-1. The control treatment had the lowest value (3.987) t/h-1.